(NsEMNADCATX MGNOWENIJ WESNYs - Yulian Semenov (Saint Petersburg (NaZBUKAs, 2021)
(N`LIAN sEMENOWI^ sEMENOW (B- (NRUSSKIJ SOWETSKIJ PISATELX(B, (NISTORIK(B, (NVURNALIST(B, (NPO\T(B, (NAWTOR KULXTOWYH ROMANOW O {TIRLICE(B, (NLEGENDARNOM SOWETSKOM RAZWED^IKE(B. (NmAKS oTTO FON {TIRLIC (B((NPOLKOWNIK mAKSIM mAKSIMOWI^ iSAEW(B) (NZAWOEWAL L@BOWX MILLIONOW ^ITATELEJ I STAL PO(B-(NNASTOQ]EMU NARODNYM GEROEM(B. (No NEM RASSKAZYWA@T ANEKDOTY I PRODOLVA@T SPORITX O EGO PROTOTIPAH(B. (NbOLX[INSTWO KNIG O {TIRLICE \KRANIZIROWANY(B, (NA TELEFILXM (B"(NsEMNADCATX MGNOWENIJ WESNY(B" (NBYL I OSTAETSQ ODNIM IZ SAMYH L@BIMYH I POPULQRNYH W NA[EJ STRANE(B. (Nw KNIGU WO[LI TRI ZNAMENITYH ROMANA `LIANA sEMENOWA IZ CIKLA O {TIRLICE(B: "(NmAJOR wIHRX(B", "(NsEMNADCATX MGNOWENIJ WESNY(B" (NI (B"(NpRIKAZANO WYVITX(B".s
Keywords: Fiction; War fiction; Historical fiction